2021
DOI: 10.3390/diagnostics11071189
|View full text |Cite
|
Sign up to set email alerts
|

ACO (Asthma–COPD Overlap) Is Independent from COPD: The Case Against

Abstract: Over the last decade interest has been shown in people with symptomatic lung disease who have features both of COPD and asthma. In this review we examine how COPD and asthma are defined and examine clinical characteristics of people defined by researchers as having asthma-COPD overlap (ACO). We look at pathological and physiological features along with symptoms and consider the impact of each diagnosis upon therapeutic management. We highlight challenges in the diagnosis and management of airway disease and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 95 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…In the present study, the ACO group showed a significant decrease in both FEV 1 (L) and FEV 1 (%pred) compared to the asthma group, suggesting greater airway obstruction. Past studies have shown that both FEV 1 and FVC decrease due to smoking and exposure to other noxious inhaled insults [30]. Smoking leads to a lower FEV 1 and increased air-trapping in the lungs [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the ACO group showed a significant decrease in both FEV 1 (L) and FEV 1 (%pred) compared to the asthma group, suggesting greater airway obstruction. Past studies have shown that both FEV 1 and FVC decrease due to smoking and exposure to other noxious inhaled insults [30]. Smoking leads to a lower FEV 1 and increased air-trapping in the lungs [31].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Figure 6 of Colak and colleagues ( 7 ) shows that having an FEV 1 below 80% predicted predicts both exacerbation and mortality risk, irrespective of the presence of comorbid asthma. These data help inform the debate about the utility of ACO as a diagnostic category ( 10 ). Multiple different definitions of ACO have been proposed ( 10 , 11 ), but as defined by Colak and colleagues, self-reported and/or hospital-confirmed asthma in people with a history of cigarette smoking was associated with worse outcomes when the FEV 1 was below 80% predicted.…”
mentioning
confidence: 93%
“…These data help inform the debate about the utility of ACO as a diagnostic category ( 10 ). Multiple different definitions of ACO have been proposed ( 10 , 11 ), but as defined by Colak and colleagues, self-reported and/or hospital-confirmed asthma in people with a history of cigarette smoking was associated with worse outcomes when the FEV 1 was below 80% predicted. Although the inclusion of individuals hospitalized with an asthma exacerbation may have biased the outcomes observed, a similar pattern was seen when the individuals defined by self-reported asthma were examined.…”
mentioning
confidence: 93%
“…We believe that it is possible to produce a paper of great interest to readers. I express my deepest gratitude to the two groups of authors, Peter Calverley and Paul Walker from Liverpool, UK [ 6 ] and Naoya Fujino and Hisatoshi Sugiura from Sendai, Japan [ 7 ], who gave us the opportunity to publish pro–con reviews in this Special Issue.…”
mentioning
confidence: 99%